Grouping Behaviors of the Red Flour Beetle - Cornwell, Kinzley; Marshall, Jeremy (My University, 2018)
We studied the link between genetic and environmental factors affecting the behaviors of Red Flour Beetles. The research conducted was important because Red Flour Beetles are considered a damaging pest to the agricultural sector due to their colonization of food resources, specifically in the grain industry based upon the Agricultural Research Service, Center of Grain and Animal Health Research of the USDA. Understanding how genetic and environmental factors affect the hereditability of grouping mechanisms within the Red Flour Beetle will benefit the agricultural sector on controlling pests within their operations. At the beginning of this experiment, we believed if different strains of beetles were placed in the same conditions, then an equal delegation of genetic and environmental factors would affect the grouping of Red Flour Beetles. Based from a statement in an article from Breed and Sanchez from the Department of Ecology and Evolutionary Biology for the University of Colorado at Boulder, stating “Genes, via their influences on morphology and physiology, create a framework within which the environment acts to shape the behavior of an individual animal,” we came to the hypothesis of the experiment. Based upon the data collected, we determined that genetics alone had increasingly more of an effect of grouping behavior. These results are important because once we can determine the factors that play a role in grouping behaviors of the Red Flour Beetle, we could form products and practices that can eliminate or control their groupings within the grain industry.
Keywords: Fall 2018